The Implementation of Flipped Classroom Model in EFL Writing - Afrilyasanti, Rida (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2015)
Flipped classroom is an approach to learning to write that allows teachers to have one-on-one assistance to help learners in the “during writing” stage in the classroom. Theories are given to the students in a video lectures to watch before class. Because problems in writing mostly occur in “during writing” stage, teacher assistance is crucial. This paper aims to share theoretical review and research findings pertaining to the implementation of flipped classroom model to EFL writing. Research findings show that flipped classroom is able to give greater opportunities for interactive sessions in class which focus on the students’ own concerns, questions, and needs. Therefore, students’ difficulties in “during writing” stage can be minimized.